Gambaran Pengetahuan tentang HIV AIDS dan Kepatuhan Terapi ARV pada Pasien ODHA di Rumah Sakit Situbondo - Sasi, Nugroho Pamungkas; Ardiana, Anisah; Kurniawan, Dicky Endrian; Purwandari, Retno; Kurniawati, Yulia (Poltekkes Kemenkes Gorontalo, 2024)
Background: Seeing the high number of HIV AIDS cases in Situbondo, researchers wanted to know the description of PLWHA's knowledge about HIV AIDS and the compliance of PLWHA at Situbondo Hospital undergoing ARV therapy in an effort to identify the high incidence of HIV AIDS in Situbondo.Purpose: This research aims to analyze the level of knowledge about HIV AIDS and adherence to ARV treatment among PLWHA.Methods: This research used a quantitative descriptive method with a cross-sectional design. This study involved 128 PLWHA in one hospital (outpatient setting/care, support, and treatment center) in Situbondo and was collected by purposive sampling. Data was collected using questionnaires.Results: The study showed that 79 respondents (61.7%) or most of the PLWHA had good knowledge about HIV AIDS. The study also showed that 66 respondents (51.6%) or more than half of the PLWHA had a moderate level of compliance with ARV treatment, while 47 respondents had high satisfaction, and 15 respondents had low satisfaction.Conclusion: The level of knowledge of PLWHA about HIV AIDS who underwent ARV therapy was mostly good as much as 79 respondents (61.7%), while 36 respondents (28.1%) had a fairly good level of knowledge, and 13 respondents (10.2%) had a poor level of knowledge. The level of compliance of PLWHA in ARV treatment mostly had a moderate level of compliance as much as 66 respondents (51.6%), high compliance 47 respondents (36.7%), and low compliance15 respondents (11.7).